ANALISA KASUS ATAS PUTUSAN MAHKAMAH AGUNG NOMOR 1134/PDT/2009 TENTANG KEPEMILIKAN HAK MILIK YANG KEMUDIAN SUBJEKNYA DIKETAHUI SEBAGAI WARGA NEGARA ASING ATAS DASAR WASIAT - DARWIN DARWIN (PREMISE LAW JURNAL, 2016)
A foreign citizens cannot be ignored to be an heir as stipulated in Article 26, paragraph 3, Article 30 paragraph 2, and Article 36 paragraph 2 of UUPA the legal consequence of violating it is that the ownership will be cancelled. The result of the Case of the Supreme Court’s Ruling No. 1134 K/Pdt/2009 research shows that the procedure if signing a  will before a Notary for a foreign citizen in making a certificate should pay attention to the spa of time of the land rights by checking the identity of the foreign citizen and the other supporting documents. The list of data at the Sub-directorate of Estate in the Ministry of Law and Human Rights by giving the copy of the Will which has been made in Indonesia. The legal status of the Ownership certificate registered in the name of the defendant is recognized as the defendant’s since the land has been registered sporadically and transparent in the name of the defendant, based on the will and the man empowered to receive the will. It is also approved be the authorities such as Subdistrict Head, the National Land Board, and witnessed by the neighbors. Besides that, the defendant has changed his citizenship before the certificate is issued. The judge’s consideration in the Supreme Court’s Ruling No. 1134 K/Pdt/2009 does not give legal certainty in the administrative process of issuing the certificate. Keywords: Foreign Citizen, Ownership, Will